Strategic Sensemaking To Adaptive Defense: Leadership Centered Framework For Addressing Hybrid Threats - Lila Irawati Tjahjo Widuri; Asep Adang Supriyadi; Faonaso Harefa (UNIVERSITAS PAKUAN, 2026)
The convergence of conventional, hybrid, cyber, and non-traditional threats has increased the need for defense institutions to develop adaptive capabilities beyond static doctrines, force structures, and material modernization. This study examined the mechanisms through which strategic leadership influences national defense adaptation and asked how this relationship is shaped by organizational inertia and strategic culture. Existing studies have generally treated strategic leadership and defense adaptation as separate constructs and have not sufficiently explained how leadership cognition is translated into institutional and operational capabilities, particularly within developing and archipelagic states. To address this gap, the study employed a qualitative hybrid narrative-integrative review combining a semi-systematic literature search, thematic synthesis, theoretical triangulation, and mechanism-based conceptual framework development. The analysis identified three sequential but iterative mechanisms: strategic cognition, organizational learning, and resource orchestration. Strategic cognition enabled leaders to interpret and prioritize multidimensional threats, organizational learning institutionalized these interpretations into doctrine, routines, and organizational memory, and resource orchestration aligned personnel, budgets, technology, logistics, structures, and partnerships with strategic priorities. Organizational inertia and strategic culture were found to condition each stage by facilitating, delaying, distorting, or preventing adaptation. This study contributes to defense and strategic leadership literature by integrating upper echelons theory and the dynamic capabilities framework into a testable leadership-centered model of defense adaptation. It concludes that adaptive defense capability depends not merely on resource possession but on leaders’ ability to interpret change, institutionalize learning, and coherently mobilize resources, providing a diagnostic foundation for strengthening Indonesia’s defense policy and institutional resilience.